4
$\begingroup$

I have this series I need to calculate: $$\sum_{n=1}^\infty \frac{n+1}{n(n+2)^2}$$ I've been trying to simplify the fraction via partial fraction decomposition, and I know I somehow need to make use of the Basel Problem, meaning that $$\sum_{n=1}^\infty \frac{1}{n^2} = \frac{\pi^2}{6}$$ , but I don't know how to adress the movement of the index $n$ by $2$ in my original problem.

Any tips of how to proceed from here?

$\endgroup$
  • $\begingroup$ Don't know if it helps, but what about $$\sum_{i=2}^\infty {\frac{i}{(i-1)(i+1)^2}}=\sum_{i=2}^\infty {\frac{i}{i^3+i^2-i-1}}$$ $\endgroup$ – Dr. Mathva Mar 31 '19 at 9:24
5
$\begingroup$

Write (for example using Partial-fraction decomposition) $$\frac{n+1}{n(n+2)^2} = \frac{1}{2(n+2)^2}+\frac{1}{4}\left(\frac{1}{n}-\frac{1}{n+2}\right).$$ The second bracket summed is a telescoping sum, specifically $$\sum_{n=1}^k\frac{1}{n}-\frac{1}{n+2}=\left(\frac{1}{1}-\frac{1}{3}\right)+\left(\frac{1}{2}-\frac{1}{4}\right)+\left(\frac{1}{3}-\frac{1}{5}\right)+\left(\frac{1}{4}-\frac{1}{6}\right)+\dots+\frac{1}{k}-\frac{1}{k+2},$$ which after canceling terms gives $$\sum_{n=1}^k\frac{1}{n}-\frac{1}{n+2}=1+\frac{1}{2}-\frac{1}{k+1}-\frac{1}{k+2} \to \frac{3}{2}\,\, \text{as }k\to \infty.$$

For the first expression, notice $$ \sum_{n=1}^\infty\frac{1}{(n+2)^2}=\sum_{n=3}^\infty\frac{1}{n^2}=\sum_{n=1}^\infty\frac{1}{n^2}-1-\frac{1}{4}. $$ Can you put these together and finish?

| cite | improve this answer | |
$\endgroup$
  • 1
    $\begingroup$ yes, thank you very much. the last line was all I needed. $\endgroup$ – Avi P Mar 31 '19 at 9:32

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.